Multi-omics analysis reveals the mechanism of adventitious roots formation in peach green branch cuttings - Zhang, Fan; Ren, Jiaxuan; Wang, Chenbing (Frontiers in Plant Science, 2026)
IntroductionDuring asexual propagation of peach rootstocks, adventitious root (AR) formation is influenced by multiple factors, with exogenous hormone application being a key strategy. However, the molecular mechanisms underlying AR formation remain incompletely understood.MethodsIn this study, we treated ‘GF677’ peach rootstocks with 200 mg/L indole-3-butyric acid (IBA) and analyzed the molecular mechanism of AR formation using transcriptomic, proteomic, and metabolomic analysis.ResultsBy detecting the rooting rate and the ratio of indole-3-acetic acid-to-cytokinin (IAA/CTK), we confirmed that 21 days of treatment with 200 mg/L IBA represented the critical time point for AR formation in ‘GF677’ rootstocks. The transcriptomic analysis identified 3,305 differentially expressed genes (DEGs), the proteomic analysis revealed 1,221 differentially expressed proteins (DEPs), and the metabolomic profiling screened key metabolites, including 10 hormone-associated differential metabolites. Furthermore, KEGG pathway enrichment analysis across the multi-omics datasets identified two core co-enriched pathways: plant hormone signal transduction and biosynthesis of secondary metabolites. Through multi-omics analysis, we identified DEGs and found that genes related to auxin synthesis pathways (GRETCHEN HAGEN3 (GH3), PIN-FORMED (PIN), SMALL AUXIN-UP RNA (SAUR), AUX/IAAs, and IAA-Leucine Resistant 1 (ILR1)), CTK synthesis pathways (Cytokinin Oxidase/Dehydrogenase 7 (CKX7), Zeatin O-Glucosyltransferase (ZOG), and Isopentenyltransferase 3 (IPT3)), transcription factors related to plant hormones (Auxin Response Factor (ARF), Myeloblastosis (MYB), Myelocytomatosis (MYC), Basic Helix-Loop-Helix (bHLH), GAI-RGA-SCR (GRAS), APETALA2/Ethylene Responsive Factor (AP2/ERF), and Basic Leucine Zipper (bZIP)), and phenylpropanoid biosynthesis pathway (4-Coumarate-CoA Ligase (4CL), Phenylalanine ammonia-lyase (PAL), cinnamate-4-hydroxylase (C4H), and Flavonol synthase (FLS)) were significantly affected by IBA treatment. Quantitative real-time PCR (qRT-PCR) validation of eight key DEGs confirmed transcriptomic reliability.ConclusionThese findings suggest that IBA promotes AR formation in peach rootstocks by modulating plant hormone levels and enhancing phenylpropanoid biosynthesis.